COPRAS METHOD FOR SELECTING OPTIMAL PUBLIC TRANSPORTATION IN SURAKARTA TO SUPPORT SUSTAINABLE URBAN MOBILITY - Diansari, Brillian Nur; Agusti, Febrina; Wibowo, Dimas Satria; Ainurrahman, Arifa (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
This study aims to identify the most suitable public transportation mode in Surakarta to support sustainable urban mobility by applying the Complex Proportional Assessment (COPRAS) method. The research considers six evaluation criteria, namely convenient user, user safety, accessibility and inclusivity, fee, time efficiency, and mobility, which reflect both service quality and efficiency aspects of urban transportation. The alternatives assessed include Batik Solo Trans (BST), van, pedicab, taxi and taxibike (online and manual), representing the main public transport modes available in the city. The methodology involves normalizing the decision matrix, applying the assigned weights to the criteria, and calculating the positive and negative significance values for each alternative, followed by determining their relative significance and utility values. The findings indicate that among the alternatives, van with 100,00 achieved the highest utility value, making it the most appropriate choice for enhancing public transportation services in Surakarta. The results demonstrate that the COPRAS methos provides a systematic and balanced approach for integrating benefit and cost criteria, offering practical insights for policymakers in developing to promote efficient, inclusive, and sustainable urban transportation systems